EFEKTIVITAS SISTEM KEUANGAN DESA DALAM PERWUJUDAN E-GOVERNMENT DI DESA KEBONAGUNG KECAMATAN SUKODONO KABUPATEN SIDOARJO - Ivan Eko Hardi Pramudio; Ilmi Usrotin Choiriyah (Journal Publicuho, 2025)
This study aims to determine the effectiveness of the implementation of the Village Financial System (SISKEUDES) in supporting the realisation of e-government in Kehonagung Village, Sukodono District, Sidoarjo Regency. SISKEUDES is an application designed to enhance transparency, accountability, and efficiency in village financial management, as per the Minister of Home Affairs Regulation No. 20 of 2018. The research method used is qualitative descriptive, with data collection conducted through interviews, observations, and documentation. The results of the study indicate that although SISKEUDES has been widely implemented and provides benefits in financial recording and reporting, there are several challenges faced by village operators. These challenges include insufficient training, difficulties in adapting to system updates, and a lack of staff, which can hinder data entry into the system and the dissemination of village fund information to the public.